The Sanex WTA therapeutic exercise programme: Origins and implementation - Noble, S. (2000)
Author describes the origins and of the Sanex WTA therapeutic exercise programme in women's tennis: Professional women`s tennis has become faster and more competitive than ever before. Demands and expectations of the professional player and the sport now require defined rationales and sport-specific adaptations, which need to be included in any therapeutic exercise programme in order to enhance performance. We designed the exercise programme to: a.Restore players to full competition fitness, post injury, as quickly as possible whilst alleviating the risk of further or recurrent injury. b.Prevent injuries, including many recurrent ones. c.Enhance players` performance on court. Many of the players` problems stem from poor `core` stability, which can lead to injury through over-activity of the more powerful muscles and, therefore, increased loading of the joints etc. This pre-disposes to injury and may take power away from where it is needed, for example in shot generation. Another common underlying cause is muscle imbalance, whereby the loss of balance between muscle groups providing stability, alignment and movement can lead to dysfunction. We decided to adopt the basic principals of Comerford, in which muscles are categorised as local stabilisers, global stabilisers, and global mobilisers. Seven suggested stages for rehabilitating the sporting back (although this programme may be applied to any joint) are: 1.Setting the joint in neutral 2.Regaining dynamic control in the direction of `instability` 3.Regaining control of global stability muscle throughout range 4.Lengthening and inhibiting over-activity in the mobilising muscles 5.Train stability during overload training 6.Train stability during slow trunk/girdle movements 7.Train functional stability during high-speed limb and trunk movements. Players are assessed to determine the stage at which they will start the programme, according to their individual needs, but are expected to continue through to stage seven. Objective functional goals are set for the progression from each stage in order to provide for continuity of the programme, as players may see various Sanex WTA Tour primary health care providers (PHCP) throughout the year. Players then follow a tennis-specific therapeutic exercise programme (Ther. Ex.). They receive a printed copy of the exercises from the customised exercise software package that all Sanex WTA Tour primary health care providers can access on the road. For follow-up of players in this programme, we are setting up an encrypted, computerised tracking system, which is accessible to all Sanex WTA Tour primary health care providers. Ther. Ex. is incorporated into treatments at all tournaments. Approximately, ten tournaments a year have a designated Ther.Ex. PHCP who develops exercise programs and supervises exercise sessions. Proper exercise instruction and execution is critical to the desired outcome. In the later stages the designated PHCP also finds it important to include other tennis experts such as coaches in the programme, so that tennis-specific drills can be incorporated. The computerised tracking systems enables us to follow up and progress players Ther. Ex. programs when they are off the road, as well. Statistics will also be collected and analysed through this tracking system over the next few years, to enable us to assess the effectiveness of the Sanex WTA, SS&M departments Therapeutic Exercise Programme.